Analisis Kelayakan Ekonomi Dan Finansial Usaha Batik Papua Studi Kasus Pada Perusahaan Batik Port Numbay Papua - Indo Yama Nasarudin (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
This research analyze the economic and financial feasibility of Papua’s Batik Port Numbay. The economic performance for business was good at marketing aspect and good enough for management and human resource, production, and environment analysis aspect. While finance aspect assessment indicates that Benefit Cost Ratio (BCR) is 1,30, Value of Payback Period is 2,16 years which is below time specified 10 years. The Net Present Value is Rp 1.146.518.993, profitability index is 4,54, Internal Rate of Return (IRR) is 52,42%. Based on the overall financial measurement, it shows that the business is viable to be continued.